2020
DOI: 10.1002/adom.202001119
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplet‐Targetable Fluorescence Guided Photodynamic Therapy of Cancer Cells with an Activatable AIE‐Active Fluorescent Probe for Hydrogen Peroxide

Abstract: remarkable advantages of early diagnosis, visible drug delivery, and therapeutic efficiency, in view of its noninvasive, fast responsive, and highly sensitive properties. [2] In recent years, photodynamic therapy (PDT), which employs a photosensitizer upon light irradiation to bring about cytotoxic reactive oxygen species (ROS), has emerged as a noninvasive and reliable cancer therapeutic modality. Thanks to the inherent fluorescence of photosensitizers, PDT affords a fascinating prospect for fluorescence guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…It works on the principle that PSs can be activated in certain wavelengths to produce reactive oxygen species (ROS) with strong oxidation, so as to inactivate malignant cells and pathogenic microorganisms ( Jiang et al, 2014 ). The advantages of PDI are that it does not produce toxic chemicals, the only energy required is the light source and the possibility of causing microbial resistance is low due to its multi-target nature ( Costa et al, 2011 ), hence it has been widely applied in the fields of medicine ( Jiang et al, 2020 ), dentistry ( Rocha et al, 2020 ) and environment ( Luksiene & Brovko, 2013 ). Since the beginning of the 21st century, researchers have begun to explore the possibility of using PDI as a novel strategy for food decontamination in a non-thermal way to achieve food safety.…”
Section: Introductionmentioning
confidence: 99%
“…It works on the principle that PSs can be activated in certain wavelengths to produce reactive oxygen species (ROS) with strong oxidation, so as to inactivate malignant cells and pathogenic microorganisms ( Jiang et al, 2014 ). The advantages of PDI are that it does not produce toxic chemicals, the only energy required is the light source and the possibility of causing microbial resistance is low due to its multi-target nature ( Costa et al, 2011 ), hence it has been widely applied in the fields of medicine ( Jiang et al, 2020 ), dentistry ( Rocha et al, 2020 ) and environment ( Luksiene & Brovko, 2013 ). Since the beginning of the 21st century, researchers have begun to explore the possibility of using PDI as a novel strategy for food decontamination in a non-thermal way to achieve food safety.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the dilemma of fluorescence quenching and ROS F I G U R E 6 Chemical structures of probes for ROS weakening caused by aggregation of traditional photosensitizers, Wang and coworkers fabricated a H 2 O 2 -activatable AIE-active photosensitizer 45 for fluorescence-guided photodynamic therapy. [127] After molecule 45 was activated by H 2 O 2 overexpressed in cancer cells, the product accumulated in lipid droplets with bright AIE fluorescence and high 1 O 2 generation under light irradiation. In addition, the probe exhibited prominent features including good photostability, a large Stokes shift, and high sensitivity.…”
Section: Aiegens For Hydrogen Peroxidementioning
confidence: 99%
“…35 In addition, recent evidence demonstrated that some AIEgens could also generate reactive oxygen species (ROS) in the aggregation state upon light irradiation, making them effective photosensitizers for photodynamic therapy (PDT). [36][37][38][39][40] For instance, Tang et al rationally constructed a H 2 O 2 -responsive AIE probe TTPy-H 2 O 2 for imaging-guided organelle targeting and photodynamic cancer cell ablation. 38 Wang et al reported a LD-targeted and AIE-active photosensitizer TPECNPB for H 2 O 2 -activatable fluorescence-guided PDT on cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…38 Wang et al reported a LD-targeted and AIE-active photosensitizer TPECNPB for H 2 O 2 -activatable fluorescence-guided PDT on cancer cells. 39 Zhao et al developed an esterase-responsive prodrug (TPEQC) by conjugating an anticancer drug of chlorambucil with an AIE active photosensitizer for lysosome/mitochondria dual-targeted and image-guided cancer therapy through synergetic chemo-photodynamic cancer therapy. 40 However, a single AIEgen that is capable of the dual-imaging of mitochondria/lipid droplets, detection of cell viability and simultaneously PDT on cancer cells has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%